2022
DOI: 10.3389/fonc.2022.772615
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-Associated Macrophages: Key Players in Triple-Negative Breast Cancer

Abstract: Triple negative breast cancer (TNBC) refers to the subtype of breast cancer which is negative for ER, PR, and HER-2 receptors. Tumor-associated macrophages (TAMs) refer to the leukocyte infiltrating tumor, derived from circulating blood mononuclear cells and differentiating into macrophages after exuding tissues. TAMs are divided into typical activated M1 subtype and alternately activated M2 subtype, which have different expressions of receptors, cytokines and chemokines. M1 is characterized by expressing a la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 133 publications
0
10
0
Order By: Relevance
“…From the results, the encapsulation of nanoparticles and laser intervention improved the efficiency of drug action. In addition, M1 is characterized by the expression of a large number of induced cytokines such as TNF-α and NO, and by promoting pro-inflammatory and immune responses to exert anti-tumor activity (Gerspach et al., 2009 ; Chanmee et al., 2014 ; Qiu et al., 2022 ). The results of WB and ELISA showed that laser + CMT NPs could effectively induce macrophage typing, providing a new idea and a favorable platform for tumor immunotherapy.…”
Section: Resultsmentioning
confidence: 99%
“…From the results, the encapsulation of nanoparticles and laser intervention improved the efficiency of drug action. In addition, M1 is characterized by the expression of a large number of induced cytokines such as TNF-α and NO, and by promoting pro-inflammatory and immune responses to exert anti-tumor activity (Gerspach et al., 2009 ; Chanmee et al., 2014 ; Qiu et al., 2022 ). The results of WB and ELISA showed that laser + CMT NPs could effectively induce macrophage typing, providing a new idea and a favorable platform for tumor immunotherapy.…”
Section: Resultsmentioning
confidence: 99%
“…These precursor cells within the TME can be differentiated into active macrophages (M1 type) when stimulated by a classical pathway such as lipopolysaccharide (LPS) and IFN-γ, which exerts an antitumor effect by releasing IL-1β and cytolysin A (ClyA) or type 2 macrophages (M2) that are generated by the induction of IL-10 and TFG-β and positively enhance tumorigenesis. Moreover, the gathered findings demonstrated that TAMs found in tumor settings had a tendency to develop into M2 types when they interacted with the TME [ 98 ].…”
Section: Nf-κb Recruits and Activates Immunosuppressive Cells In Bc T...mentioning
confidence: 99%
“…These macrophages contain M1 and M2 phenotypes, while the M1 macrophages are always transformed into M2 within the BC microenvironment, and so are the monocytes [ 39 , 40 , 41 , 42 ]. Adipocytes in the breast stroma are an important source of interleukin 10 (IL-10), which also contributes to the polarization of macrophages to the M2 phenotype in BC [ 43 , 44 , 45 ]. Clinical studies have also indicated that IL-10 is an independent factor in poor prognosis in TNBC, ER-negative, or PR-negative cases [ 46 , 47 ].…”
Section: Depression Is An Important Risk Factor and Comorbidity Of Bcmentioning
confidence: 99%